ADORASI SAKRAMEN MAHAKUDUS: HIDUP KARENA DITANTANG - Ignasius Ledot (Institut Filsafat dan Teknologi Kreatif Ledalero, 2011)
Sanguis Martyrum Semen Christianorum. The blood of the martyrs is the seed of the church. This well-known expression of Tertulian concerns the growth of the faith in times of great challenge. History notes that devotion to and worship of the Eucharist has long been present in the Western Catholic tradition, and in fact has grown whenever there has been harrassment and challenge. Adoration of the Sacrament is a form of devotion that can help one to experience the presence of God in one’s life and at the same time it can be an expression of deep love of Him who has errected his tent in the midst of his people. Thus, there is a close relationship between the Eucharist and devotion. Nevertheless, it must be remembered that eucharistic devotion must never replace the liturgical celebration of the Eucharist. In the order of ecclesial values, the liturgical celebration of the Eucharist has the first and highest place. Keywords: Adorasi, liturgi, devosi, gereja, sakramen mahakudus, penghormatan, ekaristi, puncak.